(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper we present an overview of approaches for Speaker recognition. Speaker recognition is the process of automatically recognizing a person on the basis of individual information included in speech signals. Voiceprint Recognition System also known as a Speaker Recognition System (SRS) is the best-known commercialized forms of voice Biometric. The Speech is most essential & primary mode of Communication among of human being. In this paper we are focus on speaker identification and various feature extraction methods used for speaker identification system.